A resilience measure to guide system design and management - Ferris, Timothy L. J. (IEEE, 2019)
This paper presents a measure of resilience which can guide system design and management. Systems design must incorporate resilience to provide stakeholders with the most appropriate solution for their life-cycle needs. Design of resilient systems demands a measure of the resilience afforded by a system proposal which can be used to compare design proposals. The measurement method should balance the interest in resilience with all other proposal evaluation criteria, and incorporate the effect of the sequence of unknown future events affecting the system. Ideally, the resilience measure should also be useful to guide management decisions re maintenance or upgrade during the system life. This paper presents a method to measure system resilience which can be applied to engineered systems in general, not just a specific class of systems, is threat type agnostic, and does not presuppose any ‘desirable’ outcome allowing a system specific determination of ‘desirable’ outcomes.
Keywords: Measurement; System resilience; Systems design; Systems analysis